Family Pesantren Synergy Forms Students Islamic Character: Sinergi Keluarga Pesantren Membentuk Karakter Islami Santri - Adriyansyah Adriyansyah; Amilda Amilda; Fitri Oviyanti (Halaqa: Islamic Education Journal, 2026)
General Background: Islamic character education requires continuous value internalization through interconnected educational environments. Specific Background: In pesantren education, families and Islamic boarding schools both contribute to shaping students’ religious discipline, moral responsibility, social manners, and environmental awareness. Knowledge Gap: Previous studies have generally discussed family or pesantren roles separately, while concrete and sustainable synergy between both environments in strengthening students’ Islamic character remains limited. Aims: This study analyzes the synergy between family and pesantren environments and describes its contribution to students’ Islamic character formation. Results: The findings show that synergy is built through new student admission orientation, guardian meetings, quarterly tasmi’ bil ghoib, tahfiz graduation, Isra Mi’raj commemoration, and Haflah Muwadda’ah. These activities create shared educational vision, continuous communication, parental participation, spiritual motivation, and emotional support. The synergy contributes to students’ Islamic character across four dimensions: relationship with Allah, relationship with self, relationship with others, and relationship with the environment. Novelty: This study presents family and pesantren synergy as a dual reinforcement system that integrates habituation, role modelling, communication, supervision, and parental involvement in students’ daily character development. Implications: Pesantren should strengthen systematic parent mentoring and communication programs, while families should consistently continue Islamic value habituation at home to maintain integrated, sustainable, and deeply internalized character education. Highlights • Family and pesantren cooperation develops through structured religious and educational activities.• Students show stronger spiritual responsibility, discipline, social manners, and environmental care.• Continuous communication and parental involvement support deeper value internalization. Keywords Family Synergy; Pesantren Education; Islamic Character; Student Development; Character Education